Ethical Care of the Self and the Teacher in the Pedagogical Relationship: Reflections Based on the Latest Foucault - Pagni, Pedro Ângelo [UNESP] (Ministry Education & Science, 2013)
Our conception of education is that it is the responsible action whereby man becomes human, trains and faces the challenges that life and the world present, as man enters a larger, shared cultural tradition and thus joins the world. However such sharing implies that we must not just rely on tradition, but remain open to new ideas. It is essential for schooling to preserve a field where the art of living intersects with the world for which future generations are being prepared. It is in this field of intersection that this essay seeks to discuss Michel Foucault's thought, care of the self and the role played by others in the acquisition of ethical attitudes pertaining to one's conduct in life. Through reconstructing Foucault's ideas, we elaborate on the hypothesis that, before morally shaping students, teaching them values, or aiding in their skill acquisition in the sense prevailing in schooling today, it is important to understand the notion of care of the self (and how the notion implies interaction with others for effective care of the self). Care of the self is vital for thoroughly understanding the relationships between ethics and education in school. We particularly examine how Foucault's ideas and his analysis of the teacher's role in shaping the student's life conduct can help educators rethink pedagogical action in an ethical sense and find within it a certain openness to the formation of attitudes in educators and students
Keywords: ethics; care of the self; education; Michel Foucault; philosophy of education